2020
DOI: 10.2147/jir.s275595
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reactive Oxygen Species: Drivers of Physiological and Pathological Processes</p>

Abstract: Since the Great Oxidation Event, about 2.4 billion years ago, the Earth is immersed in an oxidizing atmosphere. Thus, it has been proposed that excess oxygen, originally a waste product of photosynthetic cyanobacteria, induced oxidative stress and the production of reactive oxygen species (ROS), which have since acted as fundamental drivers of biologic evolution and eukaryogenesis. Indeed, throughout an organism's lifespan, ROS affect directly (as mutagens) or indirectly (as messengers and regulators) all stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
320
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(330 citation statements)
references
References 190 publications
2
320
0
8
Order By: Relevance
“…The first is DNA damage repair (DDR) [125] . DDR allows cells to avoid accumulation of DNA damages to a point that may lead to activation of mechanisms promoting the demise of the cell(s) [126] . Induction of DDR has been demonstrated for PGK1 [54] , PFKFB3 [48] , GLUT1 [41] , and lactate [83] .…”
Section: Mechanisms Underlying Glycolysis-induced Drug Resistancementioning
confidence: 99%
“…The first is DNA damage repair (DDR) [125] . DDR allows cells to avoid accumulation of DNA damages to a point that may lead to activation of mechanisms promoting the demise of the cell(s) [126] . Induction of DDR has been demonstrated for PGK1 [54] , PFKFB3 [48] , GLUT1 [41] , and lactate [83] .…”
Section: Mechanisms Underlying Glycolysis-induced Drug Resistancementioning
confidence: 99%
“…Additionally, some herbicides, like glyphosate, 2,4-D and paraquat, at low dose, exert a hormetic response. When ROS are produced, H 2 O 2 acts as a signaling molecule that promotes cell walls malleability, allowing for inward water transport causing cell expansion [ 131 , 132 ].…”
Section: Hormesis Effects In Plantsmentioning
confidence: 99%
“…Gradually, the production of ROS became a driver of physiological and pathological processes. Low-level ROS play an important role as redox-signaling molecules in a wide spectrum of pathways that are involved in the maintenance of cellular homeostasis and regulating key transcription factors (e.g., Nrf2/Keap1, NFκB/IκB, AP-1, p53, and HIF-1) [ 132 ].…”
Section: Global Aspectsmentioning
confidence: 99%
“…Evidence showed that mitochondria are not only the major site of ROS production but also the major targets of ROS under stress [ 39 ]. Excessive ROS production can trigger mitochondrial dysfunction including the decrease in ATP generation [ 40 ], damage of respiratory chain activity [ 41 ], promoting mitochondrial membrane permeabilization, and immediately followed by the release of cytochrome c [ 42 ]. Drp1-mediated mitochondrial fission has been demonstrated to involve mitochondrial ROS production during induced cell death [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%